PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMANDIRIAN SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS SMA NEGERI 8 KOTA JAMBI - Listianti, Hardiani Fatna; Rahim, Arif (Universitas Batanghari Jambi, 2022)
This study aims to determine whether there is an effect of the Flipped Classroom learning model on students' independence in the history subject of class XI Social Sciences. This type of research is a quasi-experimental (quasi-experiment). The total population in this study was 284 people. The sampling technique in this study was random sampling, so that 35 students of class XI IPS 2 were selected as the control class and 35 students of class XI IPS 1 were selected as the experimental class. The technique of collecting data in this research is by distributing questionnaires to research respondents and documentation. The data analysis technique in this study was the t-test using the SPSS For Windows Version 16 program. The results of this study showed that (1) the results of the Pre-Test & Post-Test of the Experimental class were obtained with a total value of 4083. (2) the results of the Pre-Test scores & Post-Test Control Class obtained with a total value of 3350. And it can be seen by the analysis used using the Normality test with the results of the significance value, 0.448> 0.05. So it can be concluded that the residuals are normally distributed, and the homogeneity analysis is continued with the results of Sig. Levnc statistic > 0.05 i.e. 0.17 > 0.05. Thus, it can be concluded that the research data is homogeneous, and the Test(t) t-test is 11,174 and the value is sig 000, so, the value of Sig.000 <0.05, then H0 is rejected. H1 is accepted. That is, there is a significant effect on the use of the Flipped Classroom learning model on student independence in history subjects. Based on the results of the research that the researchers obtained, it can be concluded that there is an effect of the use of the Flipped Classroom learning model on the independence of students in the XI Social Science class history subject at SMA Negeri 8 Jambi City.